Numerical study and design equations of square and diamond bird-beak SHS T-joints under axial compression - Chen, Yu; Wang, Jiang (Thin-walled structures, 2015)
This paper presents a finite element model of square and diamond bird-beak SHS T-joints under axial compression, which was verified by the corresponding test results. The parametric study was carried out to reveal the failure modes and plasticity propagation of square and diamond bird-beak SHS T-joints. The effects of SHS brace to SHS chord width ratio (β), SHS chord width to 2 times thickness ratio (γ), and SHS brace to SHS chord thickness ratio (τ) on the ultimate strengths of square and diamond bird-beak SHS T-joints were evaluated. The typical failure modes of square bird-beak SHS T-joints were obtained from the finite element analysis, which included Brace End Buckling (BEB) and Chord Face Failure (CF). The typical failure modes of diamond bird-beak SHS T-joints were obtained from the finite element analysis, which included Brace Bending (BB), Brace End Buckling (BEB)+Chord Face Failure (CF), Chord Face Failure (CF). The bird-beak T-joints with τ=0.6–0.8 was recommend in the paper. The design equations are proposed by using multiple linear regression for square and diamond bird-beak SHS T-joints under axial compression based on the current design rules of traditional SHS T-joints given in the CIDECT. It is shown from the comparison that the joint strengths of square and diamond bird-beak SHS T-joints calculated using the proposed design equations agreed well with the finite element analysis results, which means the proposed design equations are verified to be accurate. •Bird-beak SHS T-joints under axial compression was numerically investigated.•FE model of bird-beak T-joints was verified by the corresponding test results.•The typical failure modes of bird-beak T-joints were obtained.•Effects of geometrical parameters on the static behaviour of joints were evaluated.•A series of equations of ultimate capacity for bird-beak SHS T-joints were proposed.